BIODEGRADATION OF POLYCYCLIC AROMATIC HYDROCARBON (PAH), PHENANTHRENE BY MARINE BACTERIUM THALASSOSPIRA SP. C.260 - Murniasih, Tutik; Lisdiyanti, Puspita; Yopi, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2010)
Phenanthrene is a polycyclic aromatic hydrocarbon (PAH) compound that is known to be reported toxic to marine flora and fauna. Remediation of this environmental pollutant using chemical and physical methods causes environmental issues. Bioremediation using marine has been applied to degrade such various PAH compounds. Screening of marine microorganism in degrading this recalcitrant is very importance for bioremediation application in Indonesian waters. The purpose of this study was to screen and isolate bacterial with potential application in biodegradation of phenanthrene and other harmful PAH in marine environments. Several potential bacteria strains were isolated from oil contaminated sea water in Cilacap area. Sequence analysis using 16S rRNA gene marine bacterium strain C.260 showed 96% sequence homology to sequence of Thalassospira sp. In biodegradation of phenanthrene, within 28 days experiments, this bacterium degraded 50% and 99.75% of phenanthrene in medium with and without enrichment with NPK fertilizer respectively. Using sublimation method, this bacterium also degradeds phenothiazine, fluoranthene, and dibenzothiophene.